ACCOUNTING ANALYSIS OF ONLINE BUYING AND SELLING TRANSACTIONS WITH SALAM CONTRACTS - Kholis, Nur; Mardiana, Mardiana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This article analyzes the application of the Salam Agreement in online buying and selling transactions. The Salam contract is a financial instrument in Islamic law which regulates the purchase of goods that do not yet exist or are not yet finished. This study aims to understand the appropriate accounting mechanisms for salam transactions on online platforms and assess whether these practices are consistent with Sharia principles. The study methodology includes literature studies and case analysis of various e-commerce platforms that implement Salam contracts. The findings show that although the greeting concept can be applied to online transactions, there are still several accounting challenges that require special attention, such as revenue recognition and risk management. This article recommends the development of more detailed and specific accounting standards to ensure that salam transactions in online buying and selling remain in accordance with sharia principles and applicable accounting practices.